INTERPRETASI SANTO PAULUS TENTANG PERKAWINAN DAN SELIBAT MENURUT 1 KORINTUS 7 - Siku Jata, Yohanes Fransiskus (IN VERITATE LUX, 2020)
This article to briefly introduce Paul's views on Marriage and Seeness (1 Corinthians 7). As a native Jew, Paul was carefully educated to understand the religion and culture of his ancestors. In this regard about himself he said: "the most Hebrew of the Ihrani". Therefore, Paul's thoughts on Marriage and Celibacy cannot be thought of without having a connection with Jewish concepts and culture. For Jews, marriage is a blessing, namely a gift given from God. About marriage and celibacy. Paulas does not differentiate between the two. Both are special graces or gifts from Allah. Regarding his statement: "married is good, but not married is better", does not mean to emphasize that celibacy is superior to marriage. If people choose to be celibate, that choice is not due to orders or commands, but simply because of willingness and free choice rooted in advice or advice. In other words, Paul is actually defending the position of marriage itself. And what is being discussed here is not a question of good and bad, but only between good and better.